The Teaching of Listening at The English Language Education Program of Mulawarman University During Covid-19 Pandemics - Farra syarliza; Bibit Suhatmady; Didik Sucahyo (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2022)
Listening is very important and language educators are often lacking in practical approaches, techniques, and activities that they can apply in their classrooms. The purposes of this study are to describe the implementation of Listening activities and the obstacles in implementing the activities during the Covid-19 pandemics. A qualitative case study approach was used in this research and the interview protocol and documents were utilized to collect the data. The findings of this research reveal that the teaching and learning activities conducted by the two research subjects are in the online synchronous and asynchronous mode of learning delivered through the three sequences of teaching listening namely pre-listening, whilst-listening, and post-listening which include the model, the process, and the strategies for teaching listening. In implementing activities, they involved the model, process, and strategies using videos, applications, and web platforms in different ways. Furthermore, both research subjects have similar obstacles like internet connection and mobile data which leads to the preference for the synchronous and asynchronous mode in teaching. Moreover, It is also found that the whilst-listening and the evaluation phases of listening are the biggest problems in teaching Listening